機能的ＭＲＩ中の電気刺激のためのシステム (2023)
The present disclosure relates to a system for generating a predefined electrical signal in an MR scanner for use in electrical stimulation of a subject during MRI or functional MRI of said subject, wherein said MR scanner is located inside a shielded MRI room. The system comprises a control unit to be located outside the MRI room for generating an electrical signal and an electrical to optical converter to be located outside the MRI room for converting said electrical signal to a corresponding optical signal. An optical transmitting element, such as an optical fiber, is used for transmitting the optical signal into the MRI room, and an optical to electrical converter is used for converting the optical signal to said predefined electrical signal for electrical stimulation of the subject during magnetic resonance imaging. The optical to electrical converter is configured for being located inside the MRI room and for operation during magnetic resonance imaging.